High-intensity focused ultrasound ablation of muscle in an anticoagulated swine model. Issue 1 (3rd January 2022) - Kaye, Elena A.; Solomon, Stephen B.; Gutta, Narendra Babu; Monette, Sebastien; Ezell, Paula C.; Maybody, Majid
Abstract: Introduction: Image-guided non-invasive high-intensity focused ultrasound (HIFU) has been gaining recognition in treating musculoskeletal tumors and desmoids. However, there is no consensus on the appropriate perioperative management for patients on ongoing anticoagulation who undergo HIFU ablation. Material and methods: Image-guided HIFU treatment was performed in swine on an ongoing oral anticoagulation protocol ( N = 5) in two treatment sessions seven days apart. On day one, a total of twenty locations were ablated, and on day eight, ten more muscle ablations were performed, and the animals were euthanized. Imaging, clinical examination, and histopathology were performed to investigate treated tissue for bleeding. Results: Imaging, clinical examination, and histopathology revealed either no bleeding or, in some samples, only small scattered cavities (0.2–2 mm in diameter) filled with blood. Conclusion: Noninvasive HIFU ablation of muscle may not require a coagulation profile within normal limits.